Differences in Regional Economic Prosperity: Do State Policies Matter? – An Empirical Investigation of Data from the German States - Thomas Döring; Lorenz Blume (Central European Public Administration Review, 2013)
Different regional economic theories come to different conclusions with regard to the impact of (state) policies on the economic prosperity of regions. This article provides empirical evidence that determinants like geography, urbanization, industrial mix and social capital explain 68 percent of the variation in GDP per worker among West German regions. One element that all these factors have in common is that they cannot, at least in the short run, be influenced by state policies. Determinants like infrastructure and human capital, both of which can be influenced by state policies, only account for another 11 percent of the variation in GDP.